Collective bargaining in Europe: towards an endgame. Volume I, Volume II, Volume III and Volume IV (Brussels, 2019)
"This collection of four volumes charts the development of collective bargaining since the year 2000 in the 28 EU Member States. These four volumes document how the institutions of collective bargaining have been removed, fundamentally altered or markedly narrowed in scope in all 28 EU Member States. However, there are also positive examples to be found. Some collective bargaining systems have proven more resilient than others in maintaining multi-employer bargaining arrangements. Based on the evidence presented in the country-focused chapters, the key policy issue addressed in this book is how the reduction of the importance of collective bargaining as a tool to jointly regulate the employment relationship can be reversed. The struggle to fend off the neoliberal assault on collective bargaining in Europe is moving towards an endgame. The outcome is still open."